EFPGA-based real-time HIL simulator of induction motor drive - Kosan, Tomas; Talla, Jakub; Blahnik, Vojtech (2016 17th International Conference on Mechatronics - Mechatronika (ME), 2016)
The control algorithms and their software implementation play crucial role in real-time embedded systems reliability and safety. Field programmable gate arrays (FPGA) based hardware in the loop (HIL) is a relatively new technique used for development and testing of hard real-time complex systems. The system simulator implemented in FPGA provides real time reactions to control system actuations. The aim of this work is to present the HIL simulator of a squirrel cage induction motor drive for control algorithm development and testing in real time conditions. The testing platform consists of target microcontroller unit with implemented software of IM drive control connected to real time FPGA simulator of IM drive.